URGENSI IMPLEMENTASI MANAJEMEN ORGANISASI BAGI MAHASISWA DALAM MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS - Budiyati, Endah; Nurhayati, Meti; Rihyanti, Erni (Bussman Journal : Indonesian Journal of Business and Management, 2025)
Critical thinking skills are essential competencies that students must possess to face the challenges of the academic and professional world. One strategic approach to enhancing these skills is through the implementation of organizational management within the student environment. Organizational management not only trains students in leadership, planning, decision-making, and communication, but also encourages them to think systematically, analytically, and find solutions to various organizational problems. This study aims to highlight the urgency of implementing organizational management in the context of developing students' critical thinking. The research method used is descriptive analytical. The data collection technique in this article uses literature studies. This article utilizes theories or concepts of organizational management and critical thinking. The results of the study indicate that the implementation of good organizational management can improve students' critical thinking skills. Thus, the implementation of organizational management not only impacts the sustainability of student organizations but also contributes significantly to the development of students' soft skills, particularly in the aspect of critical thinking.